ANALISIS FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN PADA PEMBELIAN SAWI ORGANIK DI FARMERS MARKET SEMARANG - Hermansyah, Dimas; Roessali, Wiludjeng; Prasetyo, Edy (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2021)
Mustard is one of the organic vegetables sold at Farmers Market. Consumer satisfaction is an important point that needs to be considered by the Farmers Market to improve its performance. This study aimed to analysis: 1). Consumer satisfaction on purchasing organic mustard at Farmers Market 2). Factors that influence consumer satisfaction in purchasing organic mustard greens at Farmers Market. This research was conducted from May to June 2021 at Farmers Market Semarang. The research used a survey method. The sampling method used is accidental sampling. Data were obtained from interviews with respondents using a questionnaire that has been prepared. The number of samples used was obtained from five times the number of questions that had been made, namely 100 respondents. The criteria for the selected respondents are consumers who have purchased organic mustard greens and are willing to be interviewed and are 20-45 years old. Methods of data analysis using quantitative methods include Importance Performance Analysis (IPA), Customer Satisfaction Index (CSI), and Logistics Regression. The results of the IPA calculation show that promotional attributes still need to be improved to meet consumer expectations, while product, price, and service quality attributes are the main priority and need to be maintained because they are in line with the expectations of Farmers Market consumers. The calculation of CSI obtained a value of 79.52% which indicates that consumers are satisfied with the organic vegetables sold. The results of Logistics Regression indicate that the variables that affect customer satisfaction are product, price, and service quality, while promotion doesn’t show a significant effect